About mentees and mentors: what kind of advanced training should young scientists receive? – A personal reflection - Scharf, Rüdiger E. (Hämostaseologie, 2020)
Comprehensive training of talented MD or PhD students and postdoctoral fellows is one of the essential requirements for a future career as an established investigator or even an outstanding scientist. Here, from personal experience, several relevant aspects are summarized including the high responsibility of the academic mentor. Specifically, the interaction of the mentor with fellows, the choice of the research project, and the impact of the mentor's personality on mentees are discussed.
Keywords: MD/PhD training programs; postdoctoral fellows; mentoring; good scientific practice; career planning